DEVELOPMENT OF A GREEN OPEN AREA BASED ON COLLABORATIVE GOVERNANCE IN KAMPUNG DAYUN SIAK REGENCY - Febrian, Ranggi (Department of Government, FISIP, Universitas Padjadjaran, 2022)
Dayun Village, Siak Regency, is an example of a village in Indonesia that successfully implements innovation for the community. One of the innovations is green open space and sports fields built based on collaboration using social responsibility (CSR) programs resulting from budget sharing between PT. Bumi Siak Pusaka BOB-Pertamina Hulu with the Dayun Village Government from the Dayun Village Fund. Not optimal CSR assistance in Dayun Village from other companies engaged in oil palm and community conflicts with companies is a different problem. Developing green open areas based on collaboration is a strategic innovation carried out by the Dayun Village Government. Seen from 3 dimensions, namely the context of the collaboration process, which is influenced by the starting conditions, facilitative leadership, and institutional design. Using qualitative methods in research with data collection techniques of observation, interviews, and documentation. The results of this study show that the lead character of the Penghulu Kampung Dayun is the dominant dimension in the development of green areas in Kampung Dayun.gb777